“We Speak English”: Language and Identity Processes in Northern Ireland’s Muslim Community - Marranci, Gabriele (Ethnologies, 2003)
AbstractLanguage is an important identity marker and is often a symbol of immigrants’ resistance to assimilation within the host societies. Indeed, by speaking their own languages, immigrants in Europe develop their transnational identities and set up defensive boundaries against possible cultural homogenisations. This is particularly relevant for Muslim immigrants, since Arabic is both an identity and a religious symbol. In many European mosques, Muslims consider Arabic as the only acceptable language. In particular the khutbat [Friday sermon] should be written and read in Arabic. In contrast, Muslims in Northern Ireland, who have developed their ummah [community of believers] in the only mosque and cultural centre they have (located in the Northern Ireland’s capital, Belfast), have selected English as their main community language. In this article, the author analyzes the reasons that have brought this Muslim community to use English as a complex metaphor of their peculiar social-cultural position within Northern Irish society.